Pengembangan Seni Pertunjukan untuk Pembangunan Nagari Pariwisata: Studi Kasus Festival Pasa Harau - Yuliza, Fresti; Hafid, Fauziah Sri Andria; Emely, Bamy (Institut Seni Indonesia Padangpanjang, 2024)
This article is intended to describe the development of performing arts in the tourism industry, with the material object of study being the Pasa Harau Festival in the Harau Valley, 50 Kota Regency, West Sumatra. Using the involved observation method and descriptive analysis approach, this paper describes the following: background; process; and the results of the development of performing arts for tourism purposes in that location. Research shows that tourism development in Nagari Harau is the basis for nagari development in general, because tourism is the greatest potential it has. The development of performing arts is an effort to complement the existing tourist attractions, namely natural beauty. This need then brought together various stakeholders who were then institutionalized into the Harau Valley Community and the Bintang Harau Learning Studio. The forms of performing arts development that are carried out produce works in the form of creative dances and popular musical art performances. These various works are displayed in two designed programs. Musical works are displayed through a program called Haraukustik; while contemporary performing arts are accommodated in a program called Harau Performing Arts (HarPa).